2014
DOI: 10.1007/s40195-014-0179-3
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Effects of Temperature and Strain Range on the Low Cycle Fatigue Life of a Single-Crystal Superalloy DD10

Abstract: Low cycle fatigue behavior of a nickel-based single-crystal superalloy DD10 was investigated at 760 and 980°C under different strain ranges. Results show that the fatigue life (N f ) of DD10 alloy exhibits different temperature dependence under various strain ranges. Under low strain range, the alloy exhibits a longer N f at 760°C than that at 980°C. However, under high strain range, a reverse result is obtained. This difference can be attributed to the change of dominant damage modes under various test condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies [31][32][33][34] have pointed out that a complex interaction among the operative plastic deformation mode, the loading condition and the environment affects the fatigue life of various materials. Telesman and Ghosn [35] suggested that the fatigue fracture mode depends on oxidation effects and the stress intensity during the hightemperature LCF tests in the air.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [31][32][33][34] have pointed out that a complex interaction among the operative plastic deformation mode, the loading condition and the environment affects the fatigue life of various materials. Telesman and Ghosn [35] suggested that the fatigue fracture mode depends on oxidation effects and the stress intensity during the hightemperature LCF tests in the air.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve fuel efficiency, single-crystal superalloys have been widely used [1,2] in aero engines and turbine engines. Due to the complexity of casting process and large doses of precious metal usage, single-crystal superalloys are much expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The different initiation and propagation paths of thermal fatigue cracks for the three-state specimens are schematically illustrated in Fig.11. During thermal fatigue test, thermal stress can be formed at the carbide/matrix interface due to the different thermal expansion coefficients[6,7,18,19]. In addition, these carbides are hard and brittle.…”
mentioning
confidence: 99%